Songs of America : patriotism, protest, and the music that made a nation - Meacham, Jon; McGraw, Tim (Delacorte Press, 2019)
A history of American music, exploring and celebrating the role music has played in shaping American culture and consciousness. Tracks music in the United States from the Revolution up through the Civil Rights Movement, including well-known and lesser-known songs, of patriotism and also protest.